NARROW READING IN AN EXTENSIVE READING COURSE: LEXICALLY-BASED - Siusana Kweldju (Universitas Negeri Malang, 2016)
One shot case study was conducted in one semester to undergraduate English majors who were preparing themselves to become English teachers at high school level. This study was to find out whether or not students had positive attitudes towards narrow reading, how high narrow reading helped them improve their English proficiency, and what problems students might have with narrow reading. Four questionnaires were completed during the case study to discover how students felt and thought about the course and how the course improved their English. It was found out that narrow reading not only improved students' language proficiency but also helped students develop their general knowledge, the love of reading and the appreciation on literary work.